A dual-channel chemosensor based on diarylethene bearing a benzoisothiazole unit for detecting CO32−. (March 2023) - Ma, Xinhuan; Lu, Mengmeng; Wang, Xinyao; Cui, Shiqiang; Pu, Shouzhi
Abstract: A new photochromic diarylethene with a benzoisothiazole unit has been designed and synthesized. The diarylethene could act as a colorimetric and fluorescence dual-channel chemosensor for CO3 2− with short response time, high selectivity, and excellent sensitivity. Moreover, the response mechanism of the chemosensor to CO3 2− was studied systematically in methanol. The chemosensor could be used to the detection of CO3 2− in practical water samples, and also be made into test papers for CO3 2− recognition with high efficiency. Graphical abstract: A dual-channel chemosensor has been designed and synthesized for detecting CO3 2− with excellent selectivity and sensitivity. The chemosensor could be used to detect CO3 2− in practical water samples, and be made into test strips for CO3 2− recognition with high efficiency. Image 1 Highlights: A new diarylethene derivative with a benzoisothiazole unit has been designed and synthesized. The derivative could act as a dual-channel chemosensor for CO3 2− detection with excellent selectivity and sensitivity. The chemosensor could be made into test strips for CO3 2− recognition with high efficiency.